Parascaphoidella, a new leafhopper genus from China (Hemiptera: Cicadellidae: Deltocephalinae: Scaphoideini) - Wei, Xingtao; Fang, Yongqin; Xing, Jichun (Zootaxa, 2020)
Parascaphoidella gen. nov. and two species: Parascaphoidella transversa (Li & Xing, 2009) comb. nov. (as type species) and Parascaphoidella biprocessa sp. nov. from China are described and illustrated. A key to species is also provided.